Ḥadīṡ-Ḥadīṡ dalam Kitab Kanzun an-Najah wa as-Surūr: Studi Atas Kualitas dan Pemahaman Ḥadīṡ Bab Bulan Shafar - Ramadhani, Andre; Roihan, Muhammad; Simamora, Nur Aisah (ANWARUL, 2024)
Ḥadīṡ Nabī is the main source of Islamic teachings after the Al-Qur’ān. A ḥadīṡ that is ṣaḥīḥ in terms of its sanad is not necessarily ṣaḥīḥ in terms of its mata. Sometimes he is weak in terms of his eyes, namely after the faqihs find hidden defects in him. Furthermore, ḥadīṡ Nabī does not only discuss matters of law, worship, muamalah, but ḥadīṡ Nabī also talks about prayers in everyday life. This article aims to determine the authenticity of the ḥadīṡ-ḥadīṡ in the book Kanzun an-Najah wa as-Surūr. The problem in this research is the quality of ḥadīṡ-ḥadīṡ regarding prayer and practice in the book Kanzun an-Najah wa as-Surūr chapter of the Month of Safar and ḥadīṡ’s understanding of prayer and practice in the book Kanzun an-Najah wa as-Surūr chapter of the Month of Safar. This research uses library research with the main reference being the book Kanzun an-Najah wa as-Surūr. The secondary references are the ḥadīṡ books which are included in the al-Tis’ah pole, books, journals, theses, theses, etc. The data collection technique used is the documentation method, namely collecting data based on the things discussed in the form of notes, transcripts, books, magazines, and so on. Meanwhile, in analyzing the data, the techniques used were the mauḍū’ī and naqd al-Sanad and matan methods. The research in this thesis found that the two ḥadīṡ in the Month of Shafar chapter studied had different qualities, the first ḥadīṡ had the quality of ḥasan, while the second ḥadīṡ had the quality of ḍa’īf. Likewise, the understanding of ḥadīṡ regarding prayer at the end of the month of Safar, there are differences of opinion among the ulama, some ulama allow it, such as Shaīkh ‘Abdul Ḥamīd, and others forbid it.